THE EFFECTIVENESS OF USING CARTOON VIDEOS IN TEACHING SPEAKING TO THE STUDENTS OF SMPN 2 RANTAU KALIMANTAN SELATAN IN ACADEMIC YEAR OF 2013/2014 - Nor Millah Hayati (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2018)
This thesis is purposed at proving the effectiveness of cartoon videos in teaching speaking to the Eighth Grade Students of SMPN 2 Rantau Kalimantan Selatan in academic year of 2013/2014, and showing that there is a significant difference in speaking ability between the students who were taught by using cartoon videos and those who were taught by using conventional method. This study is an experimental research. The population of this study was the eighth grade students of SMPN 2 Rantau Kalimantan Selatan in academic year of 2013/2014 which consisted of seven classes. The total number of population was 158. There were two classes taken as the sample, Class VIII B serving as control class were taught by using conventional method, while class VIII F as the experimental class were taught by using cartoon videos. Class VIII B consisted of 22 students and class VIII F consisted of 22 students. Both classes were given the pre-test at the beginning and the post-test at the end after the treatment. The data were collected by using speaking test. The data were analyzed by using t-test computation, descriptive analysis, and inferential analysis. The research findings show that there is a significant difference in students’ speaking ability between the experimental group taught by using cartoon videos and those who were taught by using conventional method. The result of the pre-test shows that both groups are poor, while the post-test result shows that the experiment group is better than the control one. The mean score of the experimental class in pre-test was 42.50 and that of control class was 42.73. The mean score in post-test of the experimental class was 75.68 and that of the control class was 57.50. It can be seen that the mean score of the experimental class was higher than that of control class in post-test. Furthermore, based on the hypothesis testing, it could be seen that the value of -t obtained (-5.245) < - t table (-2.018), at the significant level 5%. This implied that there is a significant difference of students’ speaking ability between the students who were taught by using cartoon videos and those who were taught by using conventional method.